1992
DOI: 10.1038/jcbfm.1992.12
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Antioxidants and Amino Acids in the Cortex of the Rat: Monitoring by Microdialysis of Early Ischemic Changes

Abstract: Summary: Extracellular concentrations of ascorbic acid, glutathione, cysteine, uric acid, tyrosine, and tryptophan were monitored using intracerebral microdialysis in the left frontoparietal cortex of spontaneous hypertensive rats before, and for 3 h after, either focal ischemia [left middle cerebral artery occlusion (MCAO)] or sham oper ation. The size of the ischemic area and the position of the microdialysis probe were checked using the enzyme his totopochemical acid phosphatase reaction. The probe was alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 20 publications
3
26
0
3
Order By: Relevance
“…Under normal physiologic conditions, neurologic damages mediated by ROS can be prevented by the cellular antioxidant network. However, AsA levels decrease in the brain and rise sharply in extracellular fluid of the brain after severe ischemic hypoxia (Hillered et al, 1988;Landolt et al, 1992). The nitroxide radical by itself is also an antioxidant and can be used as a superoxide dismutase mimic Figure 6 The quantification of oxidized and total (oxidized + reduced) MC-P in brain tissue and blood using X-band EPR.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiologic conditions, neurologic damages mediated by ROS can be prevented by the cellular antioxidant network. However, AsA levels decrease in the brain and rise sharply in extracellular fluid of the brain after severe ischemic hypoxia (Hillered et al, 1988;Landolt et al, 1992). The nitroxide radical by itself is also an antioxidant and can be used as a superoxide dismutase mimic Figure 6 The quantification of oxidized and total (oxidized + reduced) MC-P in brain tissue and blood using X-band EPR.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione efflux from brain cells is increased by potassium depolarization, iron (Fe 2+ ), inhibitors of mitochondrial respiration (malonate, 1-methyl-4-phenylpyridinium (MPP + ), 3-nitropropionic acid and cyanide), and after ischemia (32)(33)(34)(35)(36)(37)(38). In a previous study, we showed that the NMDA-mediated glutathione efflux was dependent on extracellular calcium but unrelated to dantrolene sensitive intracellular calcium release, osmotic change and glutathione-, or nitric oxide-synthesis (39).…”
Section: Introductionmentioning
confidence: 99%
“…Diese Beobachtung wird auch durch eine tierexperimentelle Studie an Schafen bestätigt: Neben einer geringen Astrogliose mit vereinzelten Makrophagen entlang des Einstichkanals der Mikrodialysesonden fand sich nur in einem Fall ein kleines (10 mm×1,5 mm), subkortikales Hämatom [54]. In anderen tierexperimentellen Studien dieser Methode war es sogar schwierig,die Lage des Katheters selbst unter Anwendung entsprechender Färbungen überhaupt zu lokalisieren [29]. Im Vergleich mit intraparenchymalen oder intraventrikulären ICPSonden sind die verursachten Läsionen minimal, sodass die Anlage einer Mikrodialysesonde sicher und ethisch vertretbar ist, insbesondere bei Patienten, die ohnehin ein ICP-Monitoring oder eine Kraniotomie erhalten sollen [33].…”
Section: Sicherheit Der Methodeunclassified